Desafíos de la ley 7600 ante las nuevas tendencias de la educación inclusiva - Moreira Mora, Tania Elena (2008)
In this article they analyze the historical trajectory and the theoretical perspective of the inclusive education and set out some challenges of Law 7600 in the present context of the education for all, from a bibliographical investigation on the evolution of this paradigm. The main contemporary perspective appears like: the diversity, the normalization, the human right, the values and the cross-cultural view, that consolidate the sprouting of a inclusive approach. As a result of those positions challenges of Law 7600 are indicated on the equality of the people with disability in the educative context of Costa Rica. These challenges were oriented to the development of educative projects, the cooperative work, the consolidation of values, the educational qualification and the dowry of human and material resources with an intention in common: to contribute with the exact fulfillment of the objectives of the law.